Pengaruh Literasi Keuangan, Teknologi Keuangan dan Efikasi Keuangan Terhadap Inklusi Keuangan pada Era Digital dengan Perilaku Keuangan sebagai Variabel Mediasi - Tri Wahyuni, Mira; Sucahyati, Diarany; Hari Suryaningrum, Diah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research investigates the connection between financial literacy, financial technology, financial efficacy, financial inclusion and financial behavior on the digital era. This study utilizes the theory of planned behavior (TPB). The method of gathering data applied was stratified judgmental sampling utilizing a questionnaire with a population of undergraduate accounting students in East Java resulting in 110 samples from Airlangga University, UPN Veteran Jawa Timur, and Terbuka University. PLS-SEM was employed as a technique for data analysis with produced research findings, namely financial literacy, financial technology has a positive effect on behavior and financial inclusion, and financial behavior has a positive effect on financial inclusion. In addition, financial behavior is able to mediate the effect of financial literacy and financial technology on financial inclusion. However, financial efficacy has no effect on behavior and financial inclusion and financial behavior cannot mediate the effect of financial efficacy on financial inclusion.